In vitro germination of pollen grains of three native species from Pampa biome with ornamental potential - Tedesco, Marília; Alves, Luciano da Silva; Avrella, Eduarda Demari; Simioni, Carine; Schafer, Gilmar (Comunicata Scientiae, 2020)
The aim of this work was to verify the in vitro germination of pollen grains of Angelonia integerrima L., Campomanesia aurea O. Berg and Sesbania punicea (Cav.) Benth in different culture medium and temperatures. For this purpose, flower buds from which pollen was collected and sprayed on plates containing the three evaluated culture medium: M1 - agar and sucrose; M2 - agar, sucrose and H3BO3; M3 - agar, sucrose, H3BO3, Ca(NO3), MgSO4 and KNO3; and two incubation temperatures (20 °C and 30 °C). Data was subjected to analysis of variance after its transformation to square root and means were compared by Fisher’s test (LSD). For the three species, the temperature of 30 ºC provided the highest percentage of pollen grain germination. For A. integerrima, M1 and M3 promoted the highest germination percentages (40.7 % and 56.5 %, respectively). On the other hand, for C. aurea, M2 provided the highest germination average (43.7 %). At last for S. punicea, M3 was the one that provided the highest average (31.62 %). It was concluded that the evaluated species differ in micronutrient requirements for in vitro germination of pollen grains. The temperature of 30 °C was suitable for all three species.